The Relation Between Dating Violence Victimization and Commitment Among Turkish College Women: Does the Investment Model Matter? - Toplu-Demirtas, Ezgi; Hatipoğlu-Sümer, Zeynep; White, Jacquelyn W (International Journal of Conflict and Violence (IJCV), 2013)
The present study explored the sexual, physical, psychological, and overall dating violence experiences, and related these experiences to Investment Model variables among Turkish college women. Three hundred and ninety dating women from four universities in Ankara, Turkey completed the Satisfaction, Investment, Alternatives, and Commitment subscales from the Investment Model Scale and the Sexual Coercion, Physical Assault, and Psychological Aggression subscales from the Revised Conflict Tactics Scale. 79.5 percent reported at least one incident of violence in a dating relationship within the previous year. Regression analyses indicated that satisfaction fully mediated the relations between physical, psychological, and overall dating violence victimization and commitment, but not for sexual victimization. The results suggest that future research should explore the possibility that the dissatisfaction women experience may be related to an increased likelihood of relation termination.